2019
DOI: 10.1038/s41388-019-0832-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer extracellular vesicles contribute to stromal heterogeneity by inducing chemokines in cancer-associated fibroblasts

Abstract: Cancer-associated fibroblasts (CAFs), one of the major components of a tumour microenvironment, comprise heterogeneous populations involved in tumour progression. However, it remains obscure how CAF heterogeneity is governed by cancer cells. Here, we show that cancer extracellular vesicles (EVs) induce a series of chemokines in activated fibroblasts and contribute to the formation of the heterogeneity. In a xenograft model of diffuse-type gastric cancer, we showed two distinct fibroblast subpopulations with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 46 publications
4
85
1
Order By: Relevance
“…Since CAFs conditioned media attracted more migrated cancer cells, there might be cytokines, chemokines or other factors contributing to invasion and metastasis of GC cells. Exosome can be taken up by neighboring or distant cells, subsequently leading to changes in gene expression, and it plays a crucial role in cancer biology with vesicular transport [21][22][23][24][25][26]. In our study, exosomal MMP11 was found overexpressed in gastric CAFs.…”
Section: Discussionsupporting
confidence: 48%
“…Since CAFs conditioned media attracted more migrated cancer cells, there might be cytokines, chemokines or other factors contributing to invasion and metastasis of GC cells. Exosome can be taken up by neighboring or distant cells, subsequently leading to changes in gene expression, and it plays a crucial role in cancer biology with vesicular transport [21][22][23][24][25][26]. In our study, exosomal MMP11 was found overexpressed in gastric CAFs.…”
Section: Discussionsupporting
confidence: 48%
“…We observed a very modest difference in transcript levels of adhesion molecules upon osteosarcoma cell-derived EV stimulation, implicating that EVs do not play a direct role in endothelial cell activation in vitro. However, in the current study, we did not investigate potential indirect effects, which might include EV-regulated cytokine release from other stromal cells that can drive increased adhesion or endothelial permeability [38]. Although widely used as an experimental model in cancer biology research, our in vitro model employing immortalized established cancer cell lines has several drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings support the hypothesis that the bioactive molecules encapsulated in the EVs are capable of modifying the functions of the recipient cells. Tumor-derived EVs, also referred as oncosomes due to the fact that their cargo is composed by oncogenic macromolecules (Meehan et al, 2016), have been proven to induce changes in the phenotype of neighboring as well as distant cells, promoting tumor growth and local invasion in different cancer types (Webber et al, 2015;Fang et al, 2018;Naito et al, 2019). In addition, atypically large (1-10 µm in diameter) EVs derived from amoeboid tumor cells have been recently identified in the circulation of different mouse models of prostate cancer as well as in the biological fluids of metastatic prostate cancer patients (Di Vizio et al, 2012).…”
Section: New Horizons Of Organoids Application: Modeling Evs Releasementioning
confidence: 99%